Icariin Enhances Cytotoxicity of Doxorubicin in Human Multidrug-Resistant Osteosarcoma Cells by Inhibition of ABCB1 and Down-Regulation of the PI3K/Akt Pathway - Wang, Zhendong; Yang, Lei; Xia, Yuanzheng; Guo, Chao; Kong, Lingyi (Biological & pharmaceutical bulletin, 2015)
Multidrug resistance is one of the major causes limiting the efficacy of chemotherapeutic agents used to control osteosarcoma. Multidrug resistance protein 1 (MDR1 or ABCB1) was considered to play a critical role in multidrug resistance. Agents from traditional Chinese medicines (TCMs) have great potential to prevent the onset or delay the progression of the carcinogenic process, and also to enhance the efficacy of mainstream antitumor agents. Herein, we investigated the effect and mechanism of icariin in the human osteosarcoma doxorubicin (DOX)-resistant cell line MG-63/DOX. In this study, icariin exhibited significant effects in sensitization of the resistant cancer cells at a concentration non-toxic to doxorubicin. It also increased the intracellular doxorubicin accumulation and retention in MG-63/DOX cells. In addition, an increase in Rh123 accumulation and a decrease in Rh123 efflux were observed in MG-63/DOX cells treated with icariin, indicating a blockage of the activity of MDR1. Furthermore, icariin enhanced the apoptosis induced by doxorubicin and down-regulated the expression of MDR1. The mechanism involves the inhibition of phosphatidyl inositol 3-kinase (PI3K)/Akt signaling. In conclusion, icariin possesses a reversal effect on multidrug resistance in MG-63/DOX cells through down-regulation of the MDR1 and the PI3K/Akt pathway, and has the potential to be an adjunct to chemotherapy for osteosarcoma.